The use of a pedicled buccal fat pad for reconstruction of posterior mandibular defects - Hyen Woo Lee; Sung ok Hong; Heeyeon Bae; Youngjin Shin; Yu-jin Jee (SpringerOpen, 2021)
Abstract Background The pedicled buccal fat pad has been used for a long time to reconstruct oral defects due to its ease of flap formation and few complications. Many cases related to reconstruction of defects in the maxilla, such as closing the oroantral fistula, have been reported, but cases related to the reconstruction of defects in the mandible are limited. Under adequate anterior traction, pedicled buccal fat pad can be a reliable and effective method for reconstruction of surgical defects in the posterior mandible. Case presentation This study describes two cases of reconstruction of surgical oral defects in the posterior mandible, all of which were covered by a pedicled buccal fat pad. The size of the flap was sufficient to perfectly close the defect without any tension. Photographic and radiologic imaging showed successful closure of the defects and no problems were noted in the treated area. Conclusion In conclusion, the pedicled buccal fat pad graft is a convenient and reliable method for the reconstruction of surgical defects on the posterior mandible.